Quantum adiabatic elimination at arbitrary order for photon number measurement⁎This work has been supported by ANR grant HAMROQS. Part of this work was made possible through the support of Fondation Del Duca and IDEX Lyon (Contract No. ANR-16-IDEX-0005). Issue 2 (2020) - Sarlette, Alain; Rouchon, Pierre; Essig, Antoine; Ficheux, Quentin; Huard, Benjamin
Abstract: Adiabatic elimination is a perturbative model reduction technique based on timescale separation and often used to simplify the description of composite quantum systems. We here analyze a quantum experiment where the perturbative expansion can be carried out to arbitrary order, such that: (i) we can formulate in the end an exact reduced model in quantum form; (ii) as the series provides accuracy for ever larger parameter values, we can discard any condition on the timescale separation, thereby analyzing the intermediate regime where the actual experiment is performing best; (iii) we can clarify the role of some gauge degrees of freedom in this model reduction technique.